Voice controlled music player android app - Chong, Zheng Kit (2022)

(untitled)
In this project, an android music player application will be developed. This music player’s specialty is that the users can voice control the music player. However, users can use the music player as a normal music player too. This music player can scan the phone storage for the list of the songs and are consist of basic function that a music player possessed. Users can control the music player through the voice command button or using the interface of the music player. By speaking the voice command to the phone, the application will carry out its function based on the command such as play and pause. Users will be able to give out the voice command even if they are in the interface of the other application since the voice command button will stay on the screen if the user did not terminate the application. The interface of this application is very simple as it does not require time for the users to understand how the application works. In this project the waterfall methodology is being implemented. There are 4 basic phases of this methodology, which is the Analysis Phase, Design Phase, Implementation Phase and lastly Testing phase. Through these 4 phases, the project can develop in the smoother pace.